International Law in the Sudanese War 2023: An Overview of the Conflict and Law Enforcement - Gunawan, Yordan; Putra, Muh Raqi Pratama; Khairi, Muh Faqih Al; Arumbinang, Mohammad Hazyar (Universitas Negeri Surabaya, 2024)
In early 2023, Sudan faced significant turmoil primarily driven by a civil war involving prominent military factions. The conflict stemmed from a power struggle and ideological differences between General Abdel Fattah Al Burhan, who assumed leadership of the armed forces and presidency, and his deputy, General Mohamed Hamdan Dagalo, who also heads the Paramilitary Rapid Support Force (RSF). This research aims to analyze the Sudanese conflict's impact on the population and the role of international law in addressing violations during the crisis. The war has exacted a heavy toll on Sudanese civilians, resulting in substantial loss of life and exacerbating humanitarian crises across the country. International law emerges as a crucial avenue for holding accountable those responsible for violations, encompassing both military and civilian populations. Employing sociolegal juridical methods, this study examines existing data pertaining to the Sudanese conflict and scrutinizes how international organizations enforce legal standards within this context. By leveraging international legal frameworks, this research advocates for applying legal sanctions to address violations committed by the Sudanese government and associated military factions. This approach seeks to provide legal recourse and justice for affected civilians while highlighting the imperative of international law in fostering accountability and peace amid ongoing conflict.